Implication of Oxidative Stress in Fetal Programming of Cardiovascular Disease - Rodríguez-Rodríguez, Pilar; Ramiro-Cortijo, David; Reyes-Hernández, Cynthia G.; López de Pablo, Angel L.; González, M. Carmen; Arribas, Silvia M. (Frontiers in Physiology, 2018)
Lifestyle and genetic background are well known risk factors of cardiovascular disease (CVD). A third contributing factor is suboptimal fetal development, due to nutrient or oxygen deprivation, placental insufficiency, or exposure to toxic substances. The fetus adapts to adverse intrauterine conditions to ensure survival; the immediate consequence is low birth weight (LBW) and the long-term effect is an increased susceptibility to develop CVD in adult life. This process is known as Developmental Origins of Health and Disease (DOHaD) or fetal programming of CVD. The influence of fetal life for the future cardiovascular health of the individual has been evidenced by numerous epidemiologic studies in populations suffering from starvation during intrauterine life. Furthermore, experimental animal models have provided support and enabled exploring the underlying mechanisms. Oxidative stress seems to play a central role in fetal programming of CVD, both in the response of the feto-placental unit to the suboptimal intrauterine environment and in the alterations of physiologic systems of cardiovascular control, ultimately leading to disease. This review aims to summarize current knowledge on the alterations in oxidative balance in response to fetal stress factors covering two aspects. Firstly, the evidence from human studies of the implication of oxidative stress in LBW induced by suboptimal conditions during intrauterine life, emphasizing the role of the placenta. In the second part we summarize data on specific redox alterations in key cardiovascular control organs induced by exposure to known stress factors in experimental animals and discuss the emerging role of the mitochondria.